The Misuse of Anabolic-Androgenic Steroids among Iranian Recreational Male Body-Builders and Their Related Psycho-Socio-Demographic factors - Hooman ANGOORANI; Farzin HALABCHI (Tehran University of Medical Sciences, 2015)
Background: The high prevalence and potential side effects of anabolic-androgenic steroids (AAS) misuse by athletes has made it a major public health concern. Epidemiological studies on the abuse of such drugs are mandatory for developing effective preventive drug control programs in sports community. This study aimed to investigate the prevalence of AAS abuse and their association with some psycho-socio-demographic factors in Iranian male recreational body-builders. Methods: Between March and October 2011; 906 recreational male body-builders from 103 randomly selected bodybuilding clubs in Tehran, Iran were participated in this study. Some psycho-socio- demographic factors including age, job, average family income, family size, sport experience (months), weekly duration of the sporting activity (h), purpose of participation in sporting activity, mental health as well as body image (via General Health Questionnaire and Multidimensional Body-Self Relations Questionnaire, respectively), and history of AAS use were obtained by interviews using questionnaires. Results: Participants were all recreational male body-builders [mean age (SD): 25.7 (7.1), ranging 14-56 yr]. Self-report of AAS abuse was registered in 150 body-builders (16.6%). Among different psycho-socio-demographic factors, only family income and sport experience were inversely associated with AAS abuse. Conclusion: Lifetime prevalence of AAS abuse is relatively high among recreational body-builders based on their self-report. Some psycho-socio-demographic factors including family income and sport experience may influence the prevalence of AAS abuse.   Keywords: Anabolic agents, Ergogenic, Doping, Iran, Body-building, Sports, Athlete